Analisis Sensitifitas Distribusi Kala Ulang dari Metode Plotting Position. - Ahmad Zakaria (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2013)
Frequency analysis method is the method of probability is often used in the field of civil enginee -ring. By using the method, events of the extreme values can be predicted. A standard techniquesthat often used in extreme value is plotting order-rangked data. Since a long time, researchers andpractitioners doing the study to get the best method of the plotting position.The purpose of this research is to analyze the sensitivity of the frequency distribution of return pe -riod (Tr) and Log (Tr) of the plotting position methods. The Data used in this research is in theform of annual maximum daily rainfall data. Sensitivity analysis done by comparing statistical pa -rameters of multiple frequency distribution of return period (Tr), Log (Tr) and rainfall data.From the results of this study indicated that, the correlation of the distribution frequency when re -setting the Log (Tr) with the data of the annual maximum daily rainfall gives a much better resultthan on the frequency distribution of correlation times reset Tr with annual maximum daily rain-fall. This means that the use of the frequency distribution of the return period Log (Tr) will givemore accurate extreme values.